Analysis of Rusunawa Development in the West Surabaya Area for Low-Income Communities (Lic) Reviewed from the Point of Investment and Finance - Hardaningrum, Farida; Munir, Misbakul; Bahaswan, Rizal (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
The provision of rental flats (Rusunawa) in the city of Surabaya is still constrained by location and high prices. The Surabaya City Government plans to provide high-rise housing to meet the need for decent and cheap housing for low-income communities. Analysis is needed to determine the needs of Rusunawa in the West Surabaya area through the applicant analysis process, unit and block needs, analysis of potential asset land, analysis of Rusunawa design, and investment analysis of basic rental rates for Rusunawa. The analysis results show that 6 blocks of Rusunawa are needed with 342 units per block and 10 floors per block with potential land locations on the Persil 19 and GS 172/U/1991 asset land. Technical and non-technical recommendations for the construction of Rusunawa in the West Surabaya area can be said to be feasible and the ideal rental rate for residents of Rusunawa in the West Surabaya area is IDR 343,000.